Electromagnetic Fields of Magnetospheric ULF Disturbances in the Ionosphere: Current/Voltage Dichotomy. Issue 1 (8th January 2019) - Pilipenko, Vyacheslav A.; Fedorov, Evgeniy N.; Hartinger, Michael D.; Engebretson, Mark J.
Abstract: A circuit analogy for magnetosphere‐ionosphere current systems has two extremes for drivers of ionospheric currents: the "voltage generator" (ionospheric electric fields/voltages are constant, while current varies) and the "current generator" (current is constant, while the electric field varies). Here we indicate another aspect of the magnetosphere‐ionosphere interaction, which should be taken into account when considering the current/voltage dichotomy. We show that nonsteady field‐aligned currents interact with the ionosphere in a different way depending on a forced driving or resonant excitation. A quasi‐DC driving of field‐aligned current corresponds to a voltage generator, when the ground magnetic response is proportional to the ionospheric Hall conductance. The excitation of resonant field line oscillations corresponds to the current generator, when the ground magnetic response only weakly depends on the ionospheric conductance. According to the suggested conception, quasi‐DC nonresonant disturbances correspond to a voltage generator. Such ultralow frequency (ULF) phenomena as traveling convection vortices and Pc5 waves should be considered as the resonant response of magnetospheric field lines, and they correspond to a current generator. However, there are quite a few factors that may obscure the determination of the current/voltage dichotomy. Key Points: Quasi‐DC driving of FAC corresponds to voltage generator, when ground response is proportional to ionospheric conductance Resonant driving corresponds to current generator, when ground response weakly depends on local ionospheric conductance Dayside TCVs and Pc5 ULF waves should be considered as a result of current generator